1995
DOI: 10.1111/j.1365-2362.1995.tb01967.x
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 fatty acids suppress the enhanced production of 5‐Iipoxygenase products from polymorph neutrophil granulocytes in cystic fibrosis

Abstract: Pulmonary damage in cystic br osis (CF) is associated with chronic inflammation mediated in part by proinflammatory 5-lipoxygenase products (5-LOP, leukotrienes and 5-hydroxyeicosatetraenoic acid) from polymorph neutrophil granulocytes (PMN). The authors studied 5-LOP formation of PMN from CF patients and in vitro effects of added eicosapentaenoic acid (EPA) and fish oil. Circulating PMN were isolated from 10 CF patients without acute infections and 10 control persons of the same age (4-20 years). Total 5-LOP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 16 publications
0
22
1
Order By: Relevance
“…In addition, because of the significant differences in phospholipid compositions and metabolism between mice and people, detailed analysis of compositions of phospholipid molecular species from human cells expressing mutant CFTR is essential to evaluate the potential clinical relevance of any of the results found in mouse models of CF. Administration of 22:6 n-3 to children with CF has great potential benefit as an anti-inflammatory therapy (28), but the possibility that this intervention may correct a basic defect of CFTR function requires more careful study both in mice and in patients with CF. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, because of the significant differences in phospholipid compositions and metabolism between mice and people, detailed analysis of compositions of phospholipid molecular species from human cells expressing mutant CFTR is essential to evaluate the potential clinical relevance of any of the results found in mouse models of CF. Administration of 22:6 n-3 to children with CF has great potential benefit as an anti-inflammatory therapy (28), but the possibility that this intervention may correct a basic defect of CFTR function requires more careful study both in mice and in patients with CF. …”
Section: Discussionmentioning
confidence: 99%
“…Some of these molecules were effective in acute infl ammation models but failed to offer protection in chronic models of infl ammation in experimental animals and in clinic [16,26,30,31]. Reports exist to suggest that long chain fatty acids [32,33] and molecules like α-Tocopherol [34] with long carbon chain can inhibit 5-lipoxygenase, albeit, with weak II-potency. Through extensive medicinal chemistry efforts, we have discovered RBx 7796 (Clafrinast) -a distinct chemical entity from N-hydroxyurea, that inhibits 5-lipoxygenase enzyme in a competitive manner and exhibits effi cacy in several experimental animal models of airway infl ammation.…”
Section: Introductionmentioning
confidence: 99%
“…Arachidonic acid-5, 6,8,9,11,12,14, H(n) (180-240 Ci/ mmol), 4,7,10,13,16,19-DHA-1-14 C (40-60 mCi/mmol), fatty acid-free bovine serum albumin (BSA), lipopolysaccharide from Pseudomonas aeruginosa (LPS), Histopaque 1077 and various classes of products not otherwise specified were purchased from Sigma Chemical Company (St. Louis, MO, USA). RPMI 1640, fetal bovine serum (FBS), penicillin and streptomycin were obtained from Hyclone Europe Ltd. Dextran T-70 was obtained from Pharmacia Pfizer Italy.…”
Section: Methodsmentioning
confidence: 99%
“…CF is also associated with an imbalance in the ratio of essential PUFA owing to decreased levels of linoleic and docosahexaenoic acid (n3C22:6; DHA) and to a variable excess of arachidonic acid (n6 C20:4; AA) [5,6]. Several lines of evidence suggest that these abnormalities of AA and DHA pathways are primary in CF [5][6][7][8] and many studies have suggested that supplementation with fish oils may be beneficial for reducing excessive inflammation in the disease [1,2,9,10]. Because AA competes with DHA for the same enzymes and for the site of esterification at the sn-2 position of phospholipids, it has been hypothesized that an increase in the content of DHA in the membrane can decrease the proinflammatory response triggered by AA cascade pathway, reducing the production of eicosanoids during inflammatory processes [1,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation